PENGARUH LIKUDITAS DAN KEPEMILIKAN SAHAM TERHADAP AGRESIVITAS PAJAK - Kurniawan, Agung; Amanah, Lailatul (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2022)
This research aimed to examine effect of liquidity, institusional ownership, managerial ownership, and public ownership on tax agressivesness of primary consumptive goods of manufacturing companies that were listed on Indonesia’s Stock Exchange (IDX) from 2017-up to 2020. The research was quantitative with purposive sampling as the data collection technique. In the line with that, there were 124 samples from 31 companies that were listed on Indonesia’s Stock Exchange (IDX) from 2017-up to 2020. Moreover, the data analysis technique used multiple linear regression with SPSS (Statistical Product and Service Solution) 25. The research result concluded that liquidity had a positive effect on tax aggressiveness with a significance of 0,000 < 0,050 and a coefficient of 5,468. Likewise, institusional ownership had a positive effect on tax aggressiveness with a significance of 0,000 < 0,050 and a coefficient of 11,352. On the other hand, managerial ownership did not effect on tax aggressiveness with a significance of 0,370 > 0,050 and a coefficient of -0,900. Similarly, public ownership did not effect on tax aggressiveness with a significance of 0,477 > 0,050 and a coefficient of 0,714.